(untitled) (Revista Rupturas, 2020)
The image “young people are the future” is usually used in the field of political participation to designate a supposed group based on age criteria. The research herein is based on participant observation in two Costa Rican cantons during the first round of the 2018 elections; it was possible to demonstrate that this image is negotiated, attributed and assumed in a relational manner in differentiated environments. In other words, there is no prior environment for political participation in which people considered young decide or not to get involve; on the contrary, it emerges and mutates throughout the political campaign. In the process, the electoral environment; the family and the constitution of the image of young people in the practices, are core categories when analyzing the involvement of this population in the spaces in which they operate.